Pengaruh Penggunaan Chatgpt terhadap Kompetensi Mahasiswa Pascasarjana - Chika Amalia Azhari; Arita Marini; Rihlah Nur Aulia (Lembag, 2025)
This study aims to review the literature on the effects of using ChatGPT on postgraduate students' competencies. The method applied in this study is a literature review of 420 journals from 500 journals. References were obtained from the Emerald Journal, Elsevier and Google Scholar by utilizing the Publish or Perish application. Data processing uses the VOSviewer application. With this literature review, it was found that.In the network visualization data, it was found that the widest link in the largest Red cluster was GPT, Chat GPT, Ability, Artificial Intelligent, Student, Chat, Higher education which was related to Postgraduate-student. In the overlay visualization based on the year, it was found that the projection of the year of collection at the time of the study. It can be seen from the darkest keywords, namely ability, student, skill, which have a longer research projection. Meanwhile, the research projections included in the latest research are with the keywords conversation, generative ai, education, and research. The results of Density Visualization show that the keywords ChatGPT, Ability, Higher Education, and Skill are included in the most frequently conducted research results. Meanwhile, the keywords generative AI, research, challenge, opportunity, conversation, artificial intelligent are included in the least conducted research. This shows that there is a significant relationship between the keywords mentioned.The recommendations given include strengthening the policies implemented in each university in each country for the use of AI as a medium for information and data processing. In addition, training on plagiarism in the preparation of various research journals and final assignments for postgraduate students needs to be intensified. The results of this study are expected to provide insight and breadth to related agencies that these opportunities can be further developed in Indonesia.